Pengembangan Media Pembelajaran Berbasis Multimedia Interaktif Pada Mata Pelajaran Simulasi Digital Kelas X TKJ - Widia Kurniawati; Kholida Ismatulloh; Yosi Nur Kholisho (Jurnal Pendidikan Informatika (EDUMATIC), 2018)
The purpose of this study is (1) to find out the development of interactive multimedia-based learning media on digital simulation subjects of class X TKJ at SMK 3 Selong; (2) knowing the feasibility of media experts and material experts on interactive multimedia-based learning media products; (3) knowing students responses to interactive multimedia-based learning media. The research method used is the Research and Development (RD) method. The development model used in the research is Sugiyono's research and development model. Data collection used is observation, interview, and questionnaire. Data analysis techniques use qualitative and quantitative data. The results showed that the interactive multimedia-based learning media developed were very feasible to be used in the learning process. From the feasibility media experts, interactive multimedia-based learning media obtained a feasibility percentage from media experts by 89% with very decent criteria. Meanwhile, the material feasibility experts obtained a percentage of eligibility from material experts by 91% with very feasible criteria. From the students response to media feasibility in product trials obtaining a percentage of student response values by 95% with very high criteria and in the trial of usage obtaining a percentage of student response values by 94% with very high criteria.